Density Effect of Calcium Carbonate Solution on Kernel Losses in Clay Bath Unit at PT Bina Pratama Sakato Jaya - Addin Akbar; Khairul Akli; Dwi Kemala Putri; Melysa Putri; Syarie Hidayah (JURNAL ILMIAH TEKNOLOGI INDSUTRI (SAINTI), 2022)
Clay Bath is a tool to separate palm shells from Kernels using a calcium carbonate solution. Kernel Losses in the Clay Bath unit are a problem that can be detrimental to CPO Processing Industry. The effect of the density of the calcium carbonate solution can reduce the Kernel Losses. In this study, variations in the density of calcium carbonate solution were made starting from 1.092; 1,112 ; 1.136 ; 1.142 ; 1.150 g/mL. Based on the results of the study, the lowest Kernel Losses were found at a density of 1.150 g/mL with 2.57%.